2012
DOI: 10.5194/hessd-9-6023-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climatic controls on diffuse groundwater recharge across Australia

Abstract: Reviews of field studies of groundwater recharge have attempted to investigate how climate characteristics control recharge, but due to a lack of data have not been able to draw any strong conclusions beyond that rainfall is the major determinant. This study has used numerical modeling for a range of Köppen-Geiger climate types (tropical, arid and temperate) to investigate the effect of climate variables on recharge for different soil and vegetation types. For the majority of climate types the total ann… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
2
12
0
1
Order By: Relevance
“…Barron et al (2012) showed that groundwater recharge under BSh is higher for a given annual rainfall than Cfa but BSh by definition experiences a lower rainfall than Cfa (Peel et al, 2007). The majority of the areas projected to transition from temperate (C) to arid (B) under a future climate are also projected to have a reduction in recharge , the analysis of Barron et al (2012) suggests that the reduction in recharge would have been greater without the change in climate type. For a future climate of +2.4 • C, 24 % of the country is projected to change climate type.…”
Section: Discussionmentioning
confidence: 99%
“…Barron et al (2012) showed that groundwater recharge under BSh is higher for a given annual rainfall than Cfa but BSh by definition experiences a lower rainfall than Cfa (Peel et al, 2007). The majority of the areas projected to transition from temperate (C) to arid (B) under a future climate are also projected to have a reduction in recharge , the analysis of Barron et al (2012) suggests that the reduction in recharge would have been greater without the change in climate type. For a future climate of +2.4 • C, 24 % of the country is projected to change climate type.…”
Section: Discussionmentioning
confidence: 99%
“…Results summarized in Table 2 suggest slight changes in precipitation intensity with magnification factors generally less than 1 for return periods of 2, 5 and 10 years. Such changes in precipitation intensity have been shown to dramatically alter recharge [25,27,74]. Magnification factors for several sites, Site E for example, exhibit reduced magnitudes for short-duration events and increased magnitude for longer-duration events.…”
Section: Idf Curvesmentioning
confidence: 99%
“…Also, soil moisture likely decreases to levels below the wilting point as a result of high PET between rare episodic precipitation events. Thus, we anticipate that small changes in precipitation intensity, which can have a considerable impact on recharge [27] may result in a change in the R:P ratio. It is important to recognize that changes in groundwater storage, as evaluated in the MRC (Section 3.1) is not a factor in shifts in the R:P ratio as changes in dh/dt have been accounted for prior to the estimation of recharge from the groundwater hydrograph.…”
Section: R:p Ratiomentioning
confidence: 99%
See 2 more Smart Citations